Retrospective Evaluation of Cases with the Pre-diagnosis of Cystic Echinococcosis Admitted to the Microbiology Laboratory of Diyarbakır Health Sciences Gazi Yaşargil Training and Research Hospital Between 2014 and 2017 - Gülseren Samancı Aktar; Zeynep Ayaydın; Arzu Rahmanalı Onur; Ayser Uzala Mızraklı; Fikret Tekay (Türkiye Parazitoloji Dergisi, 2020)

(untitled)
Objective:Cystic echinococcosis (CE) is a zoonotic disease, which leads to morbidity and mortality worldwide. This study aimed to retrospectively evaluate the presence of anti-Echinococcus granulosus immunoglobulin G (IgG) antibodies, which were detected by indirect fluorescent antibody test in the samples that were transferred to the Microbiology Laboratory of University of Health Sciences Turkey, Diyarbakır Gazi Yaşargil Training and Research Hospital with the pre-diagnosis of CE. Moreover, gender differences with respect to positivity rates of anti-E. granulosus IgG antibodies were investigated.Methods:Anti-E. granulosus IgG antibodies, which were detected in the samples of cases with the pre-diagnosis of CE between January 2014 and December 2017, were retrospectively evaluated. Gender difference with respect to positivity rates was investigated by applying the chi-square test in cases with positive anti-E. granulosus IgG antibodies.Results:Out of the 829 serum samples, 222 (26.7%) were found to be positive for E. granulosus IgG antibodies, among which 40 (27.2%), 56 (25.5%), 51 (23.3%) and 75 (30.6%) were found to be positive in 2014, 2015, 2016 and 2017, respectively. No significant difference was found between genders amongst the cases with positive anti-E. granulosus IgG antibodies (p>0.05).Conclusion:Since CE is a major public health problem, evaluation of the presence of anti-E. granulosus IgG antibodies would be important to understand the positivity rate at the regional level.